NUTRITIONAL PARAMETERS OF SILAGE FROM FOUR SORGHUM HYBRIDS SUBMITTED TO INCREA-SING NITROGEN DOSES PARÂMETROS NUTRICIONAIS DA SILAGEM DE QUATRO HÍBRIDOS DE SORGO SUBMETIDOS A DOSES CRESCENTES DE NITROGÊNIO - Tatiana Vieira Soares; Euclides Reuter de Oliveira; Aldi Fernandes de Souza França; Régis de Paula Oliveira; Osvaldo Rodrigues Filho; Eliane Sayuri Miyagi (Ciência Animal Brasileira, 2007)
The objective of this study was to evaluate the nu-tritional parameters of silage from four forage sorghum cultivars submitted to three nitrogen rates. A randomized block experimental design was used, arranged as a 4×3 fac-torial combination (four cultivars × three nitrogen rates), with four replicates. The following cultivars were used: 1F 305; 0369 267; 0369 255; and BR 700. Nitrogen rates were: 0; 60; and 120 Kg N.ha-1 (in the form of ammonium sulfate). Tukey test (5%) was used to compare means. DM contents were different (P<0.05) between cultivars 1F 305 and 069 267, with variations from 26.23 to 29.57%. DM contents differed between the rates of 60 and 120 kg.ha-1, with means of 27.77 and 27.90% due to the treatments. NDF contents were different (P<0.05) between cultivars 1F 305 and 0369 267, with a general variation from 49.62 to 59.69%. In the same way, ADF contents were only di-fferent between cultivars 1F 305 and 0369 267, with a general variation from 229.62 to 34.68%. kg.ha-1. ADF values had the same behavior, with an overall mean of 31.69%. Hemicellulose concentration ranged from 22.53 to 23.31%; Cellulose ranged from 24.22 to 24.48%, and Lignin ranged from 6.37 to 6.46%. CP contents were di-fferent (P<0.05) between cultivars 1F 305 and 0369 267, with a general variation from 6.23 to 7.53%. Crude protein content differed between the rates of 60 and 120 kg.ha-1, with means of 6.80% (control), 6.84, and 6.91%, respecti-vely. IVDMD values did not differ (P>0.05) between cul-tivars and N rates, with means of 46.54% (control), 49.60, and 50.07% obtained with the application of 60 and 120 kg.ha-1 N, respectively. The evaluated cultivars demons-trated good chemical composition, providing good IVD-MD in the silages produced. KEY-WORDS: Chemical composition, nitrogen fertilization, nutritional value. Este trabalho teve por objetivo avaliar os parâme-tros nutricionais da silagem de quatro cultivares de sorgo forrageiro, submetidos a três doses de nitrogênio. Foi utili-zado o delineamento experimental em blocos casualizados em esquema fatorial 4x3 (quatro cultivares x três doses de nitrogênio), com quatro repetições. Cultivares utilizadas: 1F 305, 0369 267, 0369 255 e BR 700 e três doses de N: 0, 60 e 120 Kg N.ha-1 (na forma de sulfato de amô-nio). Utilizou-se o teste Tukey (5%) para a comparação das médias. Os teores de MS diferiram (P<0,05) entre as cultivares 1F 305 e 069 267, com variação de 26,23% a 29,57%. Em função dos tratamentos, os teores de MS di-feriram entre as doses de 60 e 120 kg.ha-1, com médias de 27,77% e 27,90%. Os teores de FDN diferiram (P<0,05) entre as cultivares 1F 305 e 0369 267, com variação geral de 49,62% a 59,69%. Da mesma forma, os teores de FDA também só deferiram entre as cultivares 1F 305 e 0369 267, com variação geral de 229,62% a 34,68%. kg.ha-1. Os valores de FDA apresentaram o mesmo comportamento, com média geral de 31,69%. A concentração de Hemice-lulose variou de 22,53% a 23,31%, a Celulose de 24,22% a 24,48% e a Lignina de 6,37% a 6,46%. Os teores de PB diferiram (P<0,05) entre as cultivares 1F 305 e 0369 267, com variação geral de 6,23% a ,53%. O teor de proteína bruta diferiu nas doses de 60 e 120 kg.ha-1, com médias de 6,80% (controle), 6,84% e 6,91%, respectivamente. Os valores da DIVMS não diferiram (P>0,05) entre cultiva-res e as doses de N, com médias de: 46,54% (controle), 49,60% e 50,07%, com a aplicação de 60 e 120 kg.ha-1 de N, respectivamente. As cultivares avaliadas demonstra-ram boa composição bromatológica, proporcionando boa DIVMS das silagens produzidas. PALAVRAS-CHAVES: Adubação nitrogenada, composição bromatológica, valor nutritivo.